PILGRIMAGE TOURISM AND ITS ISSUES AND CHALLENGES WITH SPECIAL REFERENCE TO NAGAPATTINAM DISTRICT - S. VIJAYANAND (ASEAN Journal on Hospitality and Tourism, 2013)
Pilgrimage tourism is that form that is exclusively or strongly motivated for religious reasons. One of the oldest types of tourism and a worldwide phenomenon of religious history, it can be differentiated into various forms. The short-term religious tourism is distinguished by excursions to nearby pilgrimage centers or religious conferences. The long-term describes visits of several days or weeks to national and international pilgrimage sites or conferences. This paper investigates pilgrimage tourism and its issues and challenges and also it analysis the basic infrastructure issues in pilgrimage sites. .Pilgrimage tourists were identified as a key factor in developing pilgrimage tourism. The primary data for this study were collected from pilgrimage tourists which engaged in pilgrimage tourism activities. Pilgrimage tourists were identified as a key factor in developing pilgrimage tourism. This research is mainly based on primary and secondary data. Secondary data required for this study was collected from different sources. This study aims to suggest measures to make pilgrimage tourism economically viable and suggest appropriate and effective promotional strategy for promoting pilgrimage tourism inVelankanni,Nagore,Thirunallar.the analysis part includes anova,chi square,t-test,cross- tabs, Friedman mean rank test. results were shown and interpretations had written in this article. this article explains the Infrastructural facilities and pilgrimage tourism avenues in nagapattinam district.